1991
DOI: 10.1007/bf02782863
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous extensive resection of the liver and the pancreas in dogs

Abstract: Mortality, morbidity, liver function and regeneration were evaluated in dogs that had undergone simultaneous major resection of the liver and the pancreas. The 10-week survival rate was only 25% in the dogs that underwent 70% hepatectomy with more than 92% pancreatectomy, and many of them died of liver failure. Long-term survival was observed in more than 60% of the dogs after 70% hepatectomy with less than 92% pancreatectomy or after 40% hepatectomy with more than 92% pancreatectomy. The liver regeneration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Interestingly, dogs subjected to 70% hepatectomy combined with pancreatectomy had delayed recovery of hepatic function and more limited regenerative capacity than dogs who underwent hepatectomy alone. The reduction in liver regeneration was proportional to the extent of the pancreatectomy, and the reduction was most dramatic when more than 90% of the pancreas was resected 67. These results demonstrate that the pancreas plays an important role in hepatic regeneration, at least partly through the release of insulin.…”
Section: Factors Affecting Hepatic Regenerationmentioning
confidence: 67%
See 1 more Smart Citation
“…Interestingly, dogs subjected to 70% hepatectomy combined with pancreatectomy had delayed recovery of hepatic function and more limited regenerative capacity than dogs who underwent hepatectomy alone. The reduction in liver regeneration was proportional to the extent of the pancreatectomy, and the reduction was most dramatic when more than 90% of the pancreas was resected 67. These results demonstrate that the pancreas plays an important role in hepatic regeneration, at least partly through the release of insulin.…”
Section: Factors Affecting Hepatic Regenerationmentioning
confidence: 67%
“…The reduction in liver regeneration was proportional to the extent of the pancreatectomy, and the reduction was most dramatic when more than 90% of the pancreas was resected. 67 These results demonstrate that the pancreas plays an important role in hepatic regeneration, at least partly through the release of insulin. Therefore, normoglycemia using insulin should be achieved before performing PVE of PH in diabetic patients.…”
Section: Diabetesmentioning
confidence: 77%
“…A collective review for this extensive surgery in Japan has shown high morbidity and mortality rates: 76% and 38%, respectively [34]. In their experimental model of dogs, Kawarada et al [35] reported that the mortality rate was high after simultaneous extensive resection of the liver and pancreas; they furthermore revealed that hepatic regeneration was markedly impaired with the additional pancreatic resection.…”
Section: Discussionmentioning
confidence: 99%
“…operations performed in each institution. 14 In laboratory studies, Kawarada et al 15 established a variety of liver and pancreas resection models using adult mongrel dogs. Their results showed that the 4-week survival rate was 40% in dogs with 70% hepatectomy and 92% pancreatectomy, with death being ascribed to hepatic failure due to poor liver regeneration.…”
Section: Hepatic Dysfunction After Hepatopancreatectomymentioning
confidence: 99%